PEMBUATAN DAN KARAKTERISASI HIDROLISAT PROTEIN DARI IKAN LELE DUMBO (Clarias gariepinus) MENGGUNAKAN ENZIM PAPAIN - Ella Salamah; Tati Nurhayati; Indah Rahayu Widadi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
African catfish (Clarias gariepinus) is important freshwater fish commodity in Indonesia. African catfish also has high protein content, which is potential to be used as protein hydrolysate. Fish protein hydrolysate offered many advantages in food, feed, agriculture, microbiology and medicinal’s field. This research aimed to determine the optimal condition for hydrolysis of African catfish protein and to characterize protein hydrolysate from African catfish. The optimal concentration of papain used for hydrolysis of African catfish protein was 5% (w/v) for 6 hours hydrolysis time and degree of hydrolysis was 35.37%. Protein hydrolysate from African catfish revealed 21.16% of yield and water content of 5.46%; ash content of 5.71%; protein content of 53.29%; and fat content of 1.94%. Protein hydrolysate from African catfish contained 15 types of amino acids, with 9 types of essential amino acids and 6 types of non essential amino acids. The highest essential amino acid composition was lysin of 5.23%, while the highest non essential amino acid composition was glutamic acid of 7.77%. Protein hydrolysate from African catfish showed protein digestibility by in vitro enzymatic hydrolysis of 98.57%.Key words: African catfish, amino acid, fish protein hydrolysate, papain